New Heaven, New Earth: Shakespeare's Antony and Cleopatra - Blits, Jan H. (Lexington Books, 2009)
Patterned after his previous books on Shakespeare's plays, Jan H. Blits's New Heaven, New Earth is a scene-by-scene, line-by-line philosophical study of Antony and Cleopatra. Combining close attention to detail with interpretive breadth, Blits approaches Shakespeare as a first-rank thinker who, master of his own thought and writing, produced plays and poetry with an infinitely conscious art, like any commonly recognized philosophical poet. Treating the play as a fully coherent whole, Blits shows that Antony and Cleopatra, as much a history play as a love story, depicts the transition from the pagan to the Christian world_from the aftermath of the collapse of the Roman Republic and the decline of the pagan gods to the emergence of the Roman Empire and the conditions giving rise to Christianity. Instead of being organized thematically, New Heaven, New Earth follows the play from beginning to end, closely examining Shakespeare's text on its own terms and not on the terms of modern literary theory. Using this approach, Blits draws significant and insightful conclusions that will satisfy the interests of scholars of politics, literature, and history alike.